2019
DOI: 10.3390/rs11121495
|View full text |Cite
|
Sign up to set email alerts
|

Remotely Sensed Spatial Structure as an Indicator of Internal Changes of Vegetation Communities in Desert Landscapes

Abstract: Desert environments are sensitive to disturbances, and their functions and processes can take many years to recover. Detecting early signs of disturbance is critical, but developing such a capability for expansive remote desert regions is challenging. Using a variogram and 15-cm resolution Visible Atmospherically Resistant Index (VARI) imagery, we examined the usefulness of the spatial structure of desert lands for monitoring early signs of habitat changes using the Riverside East solar energy zone located wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Variograms have been widely used to characterize the spatial variations inherent in remote sensing images (Woodcock et al, 1988;Wallace et al, 2000;Hamada et al, 2019). Our variogram results implied that the set of GT samples was sufficient and reliable, and was capable of capturing the spatial variance components of field-level sampling using image indices.…”
Section: Reliability Of Ground Truth Datamentioning
confidence: 66%
“…Variograms have been widely used to characterize the spatial variations inherent in remote sensing images (Woodcock et al, 1988;Wallace et al, 2000;Hamada et al, 2019). Our variogram results implied that the set of GT samples was sufficient and reliable, and was capable of capturing the spatial variance components of field-level sampling using image indices.…”
Section: Reliability Of Ground Truth Datamentioning
confidence: 66%
“…The spatial structure of a desert can predict the signs of desert change. In order to verify this, Hamada et al [121] used the variogram function generated by the VARI to provide theoretical support for the correlation between them. Furthermore, LST maps can reflect desert characteristics to a certain extent [122][123][124].…”
Section: Classical Methods Of Algorithmsmentioning
confidence: 99%
“…Since 2012, Argonne National Laboratory (Argonne) has supported the Bureau of Land Management (BLM) in developing remote sensing methodologies for long-term environmental monitoring of Palo Verde Mesa in eastern Riverside County, California, including methods for: detailed mapping of ephemeral streams Grippo 2015a, Hamada et al 2016), estimating fractional cover of desert-land surface components (e.g., trees, shrubs, litters, and bare ground) (Hamada and Grippo 2015a), evaluating erosion risk or land stability Grippo 2015a, 2015b), and characterizing vegetation alliances using spatial structure and geostatistical approaches (Hamada et al 2019). These studies showed the promise of remote sensing for monitoring changes in desert landscapes by providing information that would be difficult to obtain through field surveys.…”
Section: Introductionmentioning
confidence: 99%